DIAGNOSTIC ACCURACY OF ULTRASONOGRAPHY IN THE DIAGNOSIS OF ACUTE APPENDICITIS - Hasan, Manssor; Perveen, Sajida; Mian, Muhammad Amer (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine accuracy of ultrasonography in the diagnosis of Acute Appendicitis using histopathologic examination of resected appendix tissue as gold standard. Study Design: Cross sectional validation Study Place and Duration of Study: General Surgery Department Combined Military Hospital Lahore from 16th December 2011 to 15th June 2012. Material and Methods: The estimated sample size on 5% chance of error via WHO sensitivity and specificity calculator was 230. Consecutive (non-probability) sampling technique was used. Pre-operatively apart from other routine diagnostic work up, ultrasonography was performed by radiologist. The decision to do appendicectomy was made independent of the findings of ultrasonography. After appendicectomy, resected appendix was sent for histopathology. Two by two tables was used to determine the sensitivity, specificity, true positive and negative values, false positive and negative values and their predictive values. Data was entered in SPSS version 16 to calculate mean and standard deviation for age. Male to female ratio for positive and negative appendicectomies was calculated. Results: We found Sensitivity of USG 93.1%, Specificity 88.23 %, Positive Predictive value 93.1%, Negative Predictive value 88.23 % and Diagnostic Efficacy 91.3 %. Mean and standard deviation for age was 30.27 and 13.76 respectively. Percentages for positive and negative appendicectomies in males were 77 and 23, while in females 45 and 55 respectively. Conclusion: Ultrasonography is highly sensitive test with fair degree of specificity in diagnosing Acute Appendicitis and its routine usage will improve diagnostic accuracy.